Ranolazine in Symptomatic Diabetic Patients Without Obstructive Coronary Artery Disease: Impact on Microvascular and Diastolic Function. Issue 5 (4th May 2017) - Shah, Nishant R.; Cheezum, Michael K.; Veeranna, Vikas; Horgan, Stephen J.; Taqueti, Viviany R.; Murthy, Venkatesh L.; Foster, Courtney; Hainer, Jon; Daniels, Karla M.; Rivero, Jose; Shah, Amil M.; Stone, Peter H.; et al.
Abstract : Background: Treatments for patients with myocardial ischemia in the absence of angiographic obstructive coronary artery disease are limited. In these patients, particularly those with diabetes mellitus, diffuse coronary atherosclerosis and microvascular dysfunction is a common phenotype and may be accompanied by diastolic dysfunction. Our primary aim was to determine whether ranolazine would quantitatively improve exercise‐stimulated myocardial blood flow and cardiac function in symptomatic diabetic patients without obstructive coronary artery disease. Methods and Results: We conducted a double‐blinded crossover trial with 1:1 random allocation to the order of ranolazine and placebo. At baseline and after each 4‐week treatment arm, left ventricular myocardial blood flow and coronary flow reserve (CFR; primary end point) were measured at rest and after supine bicycle exercise using 13 N‐ammonia myocardial perfusion positron emission tomography. Resting echocardiography was also performed. Multilevel mixed‐effects linear regression was used to determine treatment effects. Thirty‐five patients met criteria for inclusion. Ranolazine did not significantly alter rest or postexercise left ventricular myocardial blood flow or CFR. However, patients with lower baseline CFR were more likely to experience improvement in CFR with ranolazine ( r =−0.401, P =0.02) than with placebo ( r =−0.188, P =0.28). In addition, ranolazine was associated with an improvement in E/septal e′ ( P =0.001) and E/lateral e′ ( P =0.01). Conclusions: In symptomatic diabetic patients without obstructive coronary artery disease, ranolazine did not change exercise‐stimulated myocardial blood flow or CFR but did modestly improve diastolic function. Patients with more severe baseline impairment in CFR may derive more benefit from ranolazine. Clinical Trial Registration: URL:http://www.clinicaltrials.gov . Unique identifier: NCT01754259.